An Alkane-Responsive Expression System for the Production of Fine Chemicals - Panke, Sven (American Society for Microbiology, 1999)
Membrane-located monooxygenase systems, such as the Pseudomonas putida mt-2-derived xylene oxygenase, are attractive for challenging transformations of apolar compounds, including enantiospecific epoxidations, but are difficult to synthesize at levels that are useful for application to biotechnological processes. In order to construct efficient biocatalysis strains, we utilized the alkane-responsive regulatory system of the OCT plasmid-located alk genes of Pseudomonas oleovorans GPo1, a very attractive system for recombinant biotransformation processes. Determination of the nucleotide sequence of alkS, whose activated gene product positively regulates the transcription of the structural genes alkBFGHJKL, on a 3.7-kb SalI-HpaI OCT plasmid fragment was completed, and the N-terminal amino acid sequence of an AlkS-LacZ fusion protein was found to be consistent with the predicted DNA sequence. The alkS gene and the alkBp promoter were assembled into a convenient alkane-responsive genetic expression cassette which allowed expression of the xylene oxygenase genes in a recombinant Escherichia coli strain at a specific activity of 91 U per g (dry weight) of cells when styrene was the substrate. This biocatalyst was used to produce (S)-styrene oxide in two-liquid-phase cultures. Volumetric productivities of more than 2 g of styrene oxide per h per liter of aqueous phase were obtained; these values represented a fivefold improvement compared with previous results.